Modification of the "Tochen Formula" to Measure the Accuracy of Endotracheal Tube Depth in Orotracheal Intubation of Neonates with Birth Weight Below 1500 Grams or Gestational Age Below 32 Weeks - Prayudijanto, Akira; Perma Iskandar, Adhi Teguh; Rohsiswatmo, Rinawati; Fauzia Wulandari, Haryanti; Yuniar, Irene; Supriyatno, Bambang (Journal of Neonatal Surgery, 2025)
Introduction: Accurate endotracheal tube (ETT) depth is crucial to prevent serious complications. The Tochen formula, commonly used in Indonesia, shows limitations in premature or low birth weight neonates due to a high rate of malposition. This study aimed to evaluate the accuracy of the Tochen formula and compare it with a modified formula for determining appropriate ETT depth in neonates weighing less than 1500 grams or with a gestational age below 32 weeks. Methods: This retrospective cross-sectional study was conducted in the Neonatology Unit of RSCM between 1 January 2023 and 31 December 2024. Inclusion criteria were neonates with a birth weight under 1500 grams or a gestational age below 32 weeks who underwent orotracheal intubation and chest X-ray to assess ETT tip position. Results: Only 22.2% of ETT placements using Tochen’s formula were accurate, versus 77.8% using the modified formula (p < 0.001). Spearman analysis showed gestational age (r = 0.996, p < 0.001) and birth weight (r = 0.792, p < 0.001) significantly influenced ideal ETT depth. Linear regression found both factors to be significant predictors (β = 0.081 and 0.108, p < 0.001 and 0.008, respectively). The modified formula yielded improved accuracy, though ICC analysis = 0.941 indicated extremely good agreement with Tochen’s. Conclusion: Gestational age and birth weight significantly influence ideal ETT depth in group. The Tochen’s formula is less accurate for this group. The proposed modification provides improved precision for ETT placement in next longitudinal study for improve validity. Nevertheless, the potential for type 1 error was noted in the significant statistical results.